Christian Moral Values and Educational Theories - Lombaerts, Herman (Acta Paedagogica Vilnensia, 2003)
Ethical and moral responsibility is based on concrete life situations in cultures changing from the static to dynamic and complex societies. Universal principles became relative, even as based on a religious tradition and a vision of the meaning of life in a spiral evolution of new challenges and decisions. Earlier Christians could rely on a stable society and church, now the emphasis is on personal decision. The priorities in the hierarchy of values have changed, and the meaning of values, including family, religion, and personal freedom, has become different. Yet Christian values have a core and specific hierarchy to express the sacred and the presence of God. The six images of educational systems, from the collectivist, individualistic, to the scientific, express the notion of the human person, and Christianity is faced with describing the meaning of its tradition in contemporary life experiences.
Keywords: values; universal principles; personal freedom; identity